Trocas comunicativas sobre a violência: experiências intersubjetivas do Movimento pela vida - AZEVEDO, Ana Paula de Mesquita (Universidade Federal do Pará, 2018)
The present research seeks to understand the communicative experience or exchanges of experiences established, in the daily life, by the people affected by the violence, from members of the Movement for Life and their narratives of pain. We start from the reflection on the world of everyday life in Schtuz (2012), in which reality is socially constructed through knowledge and the different attributions of meanings given by individuals in certain contexts. In this perspective, intersubjectivity is an essential element in the social construction of the senses. As a research object, I take the pain narratives of the Movement for Life (Movida), an entity created informally in 2005, with the purpose of hosting victims of violence in search of justice. I observe, therefore, that this relation of the members of Movida occurs through narratives of pain and communication resources that this social movement uses for its interchanges of intersubjective experiences. These resources or communication strategies used by the group are mediators of subjectivities, playing a central role in the construction of reality, by highlighting some events in the world of life. To compose this understanding of this exchange of experience, we seek in Simmel (2006) the concept of sociation, in which individuals approach each other in the search for the same end and in the understanding of the narrative of the testimony, in order to understand the necessity of the disclosure of the pain narrated by the group. In listening to five participants of Movida, we work with qualitative research, which aims to understand as a principle of knowledge and interpretation of reality construction, considering aspects of phenomenology, combining methods of participant observation research and in-depth interview. In this way, we perceive in the interviews that the members consider Movida as a place where they can share the pain and find people who understand the situation in which they find themselves. In the group, they locate similar individuals, with whom the exchanges of experiences are carried out at every encounter of Movida.